Design and fabricate name card holder for businessman and corporate use / Ahmad Azrin Hakim Abdul Aziz - Abdul Aziz, Ahmad Azrin Hakim (2022)
The purpose of this project is to design name card holder by using solidworks software and to fabricate name card holder by using 3D printing method with low cost. Nowadays cost effectiveness is the main issues in order to produce better name card holder with low cost and high quality. The design for this project had been sketch using solidworks software. Before using 3D printing, the design in solidworks file need to be converted into appropriate format, by using CURA software. This software also can estimated time consumption for your design to be done using 3D printing. Next, for the dimensions of this project. The length, width and height of this project is 85mm * 100mm x 65mm. The method used in this project for fabrication is using 3D printing machine, this is Addictive methods that be used to create 3D objects or materials. By laying down consecutive layers of material until the thing is entirely created. The project was successfully fabricated in actual size using the FDM 3D printing machine.